2021
DOI: 10.7759/cureus.16851
|View full text |Cite
|
Sign up to set email alerts
|

An Adrenocortical Carcinoma Evolving After Nine Years of Latency From a Small Adrenal Incidentaloma

Abstract: Adrenal incidentalomas (AIs) are common incidental findings in medical practice with clinical significance. Although most AIs are nonsecretory and nonmalignant, they require a short course of follow-up over one to two years to rule out malignancy or hormonal secretion according to clinical practice guidelines. However, this can result in some adrenocortical carcinomas (ACCs) being missed if they transform at a later stage or evolve slowly. Here, we report one such case of an AI, which although remained indolen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…The transformation of an initially denoted ACA to ACC has been described not only with respect to imaging characteristics but also their hormonal profile. Five tumors initially characterized as nonfunctioning ACAs transformed to cortisol-secreting ACCs similar to our case ( 6 , 7 , 10 , 12 , 13 ).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The transformation of an initially denoted ACA to ACC has been described not only with respect to imaging characteristics but also their hormonal profile. Five tumors initially characterized as nonfunctioning ACAs transformed to cortisol-secreting ACCs similar to our case ( 6 , 7 , 10 , 12 , 13 ).…”
Section: Discussionsupporting
confidence: 72%
“…In contrast to a previous retrospective study ( 17 ), ACCs found incidentally were less aggressive, presenting also better prognosis compared with the symptomatic ones ( 25 ). The clinical history of the 10 cases initially diagnosed as benign ACAs showed that only half were completely asymptomatic and could be characterized as “true AI.” In 3 patients ( 7 , 9 , 12 ) as in our case, a pre-existing atypical abdominal symptom led to the performance of further imaging, whereas in 1 case, this information was not available ( 11 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…According to our study, it might thus be hypothesized that circPHC3 could be associated with adrenal tumor formation irrespective of its benign or malignant behavior, and its altered expression could represent a common phenomenon in both benign and malignant adrenocortical tumors [ 20 ]. However, based on epidemiological observations, benign-to-malignant progression in the adrenal cortex could be a very rare event, and it is unlikely to account for the vast majority of ACC [ 50 , 51 , 52 , 53 ]. Thus, the biological relevance of our observation is unclear.…”
Section: Discussionmentioning
confidence: 99%